The Tendency of Bullying Behavior in SMP N 12 Padang and Implications for Guidance and Counseling Services - Mona Dianes; Alizamar Alizamar (Universitas Negeri Padang, 2019)
Based on the phenomenon that researchers can be in the field when conducting interviews with several guidance and counseling teachers and students find that there are students who are perpetrators of bullying, students take acts of hazing, students take the act of